Last Rampage : The Escape of Gary Tison - Clarke, James W., 1937- (Book collections on Project MUSE., 1988)
The true story of a multiple murderer, his prison escape, aided by his family, and the trail of victims left in their wake paints a chilling portrait of a killer and a troubled criminal justice system.